Analysis of Genetic, Socio-economic, and Environmental Factors in Adolescent Mental Health: A Literature Review - Deviantony, Fitrio; Kaniya, Nurul; Zahro, Fatimatus; Lestari, Aynuning Hadi (Al-Hijrah Indonesia, 2024)
Background: A person's mental health plays a significant role in their lives since it allows them to function as living creatures and carry out their daily activities. A person in good mental health is able to see their own potential, manage everyday stressors, perform efficiently, and positively impact their surroundings. Aims: This study aims to analyze the relationship between genetic, socio-economic, and environmental factors on mental health in adolescents. Methods: A review of the literature from 2019 to 2024 was conducted as part of this research technique using Pubmed and Science Direct with the keywords “mental health”, “socio-economic factors”, “genetic factors”, “adolescents